Care staff's self-efficacy regarding end-of-life communication in the long-term care setting: Results of the PACE cross-sectional study in six European countries. (April 2019) - ten Koppel, M.; Onwuteaka-Philipsen, B.D.; van der Steen, J.T.; Kylänen, M.; Van den Block, L.; Smets, T.; Deliens, L.; Gambassi, G.; Collingridge Moore, D.; Szczerbińska, K.; Pasman, H.R.W.; ,
Abstract: Background: An important part of palliative care is discussing preferences at end of life, however such conversations may not often occur. Care staff with greater self-efficacy towards end-of-life communication are probably more likely to have such discussions, however, there is a lack of research on self-efficacy towards end-of-life discussions among long-term care staff in Europe and related factors. Objectives: Firstly, to describe and compare the self-efficacy level of long-term care staff regarding end-of-life communication across six countries; secondly, to analyse characteristics of staff and facilities which are associated to self-efficacy towards end-of-life communication. Design: Cross-sectional survey. Settings: Long-term care facilities in Belgium, England, Finland, Italy, the Netherlands and Poland (n = 290). Participants: Nurses and care assistants (n = 1680) completed a self-efficacy scale and were included in the analyses. Methods: Care staff rated their self-efficacy (confidence in their own ability) on a scale of 0 (cannot do at all) to 7 -(certain can do) of the 8-item communication subscale of the Self-efficacy in End-of-Life Care survey. Staff characteristics included age, gender, professional role, education level, training in palliative care and years working in direct care. Facility characteristics included facility type and availability of palliative care guidelines, palliative care team and palliative care advice. Analyses were conducted using Generalized Estimating Equations, to account for clustering of data at facility level. Results: Thde proportion of staff with a mean self-efficacy score >5 was highest in the Netherlands (76.4%), ranged between 55.9% and 60.0% in Belgium, Poland, England and Finland and was lowest in Italy (29.6%). Higher levels of self-efficacy (>5) were associated with: staff over 50 years of age (OR 1.86 95% CI[1.30–2.65]); nurses (compared to care assistants) (1.75 [1.20–2.54]); completion of higher secondary or tertiary education (respectively 2.22 [1.53–3.21] and 3.11 [2.05–4.71]; formal palliative care training (1.71 [1.32–2.21]); working in direct care for over 10 years (1.53 [1.14–2.05]); working in a facility with care provided by onsite nurses and care assistants and offsite physicians (1.86 [1.30–2.65]); and working in a facility where guidelines for palliative care were available (1.39 [1.03–1.88]). Conclusion: Self-efficacy towards end-of-life communication was most often low in Italy and most often high in the Netherlands. In all countries, low self-efficacy was found relatively often for discussion of prognosis. Palliative care education and guidelines for palliative care could improve the self-efficacy of care staff.